The ‘one bright light’ of Life in a Dark Cell: Reading and Writing in Victorian and Edwardian English Prisons - Alice Bonzom (Cahiers Victoriens et Edouardiens)
In 2013, the Ministry of Justice’s ban on sending books to prisoners sparked a wave of protests. It was eventually declared illegal as books were deemed essential to rehabilitation. This heated debate is part of a long history of promoting—and restricting—reading practices in carceral institutions. Between the 1850s and the eve of the First World War, whether penal administrators favoured or hindered reading, prison libraries filled up and pens were put to paper. But how were the books selected? What were the prisoners allowed to read and write? What did they actually read and write? Studying the history of prison reading and writing from above and from below reveals tensions between the perception of prisoners and the reality of life behind bars. This article explores the production and consumption of a wide array of written works in the carceral world. It endeavours to show that, through the stories written and read in prison, the story and history of prisoners come to light. From escapism to protest, from moral elevation to fellowship, written words, authorised or clandestine, were (and still are) a ‘bright light’ in prisoners’ lives.